Occupational Risk Perception and Utilization of Personal Protective Equipment Among Informal Auto‐Artisans in Ghana: A Cross‐Sectional Study - Addae Boateng Adu‐Gyamfi (Health Science Reports)
ABSTRACT Background and Aims Auto‐artisans are exposed to various occupational hazards, including physical, chemical, and mechanical risks, which necessitate the consistent use of personal protective equipment (PPE). Despite the critical role of PPE in mitigating these risks, adherence remains a challenge, particularly among artisans in informal sectors. This study examines the PPE use dynamics among auto‐artisans and assesses how perceived occupational risk predicts utilization rate. Methods This cross‐sectional study involved a sample of 957 auto‐artisans in the Ashanti region of Ghana using a multi‐sampling technique. Descriptive analyses such as Pearson's chi‐square test, bivariable and multivariable logistic regression models were performed using STATA 18. Results Overall, 72.5% of auto‐artisans used PPE. Safety boots were the most used PPE (71.26%), followed by goggles (8.76%), and face/nose masks (7.9%). Among auto‐artisans who used PPE, the majority bought their own PPE (96.7%). The major reason for the non‐use of PPE was that PPE are uncomfortable to use (30.65%). Other reasons were unavailability (29.5%), having no money to buy them (17.24%), and perceptions that it is unnecessary to use PPE (14.18%). Participants who perceived their jobs as risky had higher odds of using PPE, both in the crude (COR = 2.67, 95% CI: 1.42–5.01) and adjusted model (AOR = 2.43, 95% CI: 1.26–4.68). Conclusion This study underscores a need for the Ministry of Employment and Labour Relations, the Ghana National Association of Garages, and the other labor associations to enforce compliance and ensure that employers prioritize worker safety by supplying adequate and appropriate PPE. Given that discomfort, unavailability, and financial challenges were major barriers to PPE use, it is imperative for policymakers and stakeholders to prioritize the design and distribution of ergonomic and affordable PPE tailored to the specific needs of auto‐artisans. Occupational health literacy campaigns should be intensified to educate auto‐artisans on the importance of PPE, dispel misconceptions, and address discomfort‐related concerns.